(untitled) (Research, Society and Development, 2022)
The objective was to identify the students’ opinion about the forms of pedagogical approach experienced in a Dentistry course at a public university in Northeast Brazil. In addition, we sought to obtain undergraduate students’ perceptions of teacher development practices, learning scenarios, curriculum integration, experiences in evaluation processes, possibilities for curricular flexibility and strategies for articulating teaching, research and extension. This is a descriptive study with a qualitative approach through the application of an interview using a semi-structured script based on a validated instrument with a focus on the Pedagogical Approach dimension. Data concerning 13 students were collected, transcribed and analyzed during the academic semester of the research. Participants were randomly selected and linked to at least one of the ten semesters of the undergraduate course. It was observed that traditional methodologies are still predominant in the course and the teacher is associated with the role of transmitter of knowledge. It described the need to overcome some challenges for the curricular integration of contents and curricular components in the current curriculum. The need for changes in the arrangement of the workload and a better management of academic schedules was perceived. Although there is an importance of the articulation between teaching, research and extension, they do not understand that there is an integration between these three branches. The resolution of negative aspects associated with the improvement of existing positive conditions can contribute to a dental education more applicable to reality.